2020
DOI: 10.1155/2020/4130643
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Corneal Findings and Disease Severity in Keratoconus per Scheimpflug Corneal Tomography

Abstract: is properly cited.Purpose. is study aims to correlate the clinical signs of keratoconus (KC) which include superficial apical scarring, Fleischer rings, and Vogt striae with best spectacle-corrected visual acuity (BSCVA) and corneal tomography findings. Patients and methods. A retrospective observational study. 72 consecutive KC patients seen by the senior author over the course of one year were included in this case series. Eyes with pellucid marginal degeneration, postrefractive ectasia, history of a corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
(25 reference statements)
0
10
0
1
Order By: Relevance
“…If we use the combination therapy method, when using atropine eye drops, and also use OK lens or myopia defocus treatment, the choroidal thickening will be greater, and the effect of myopia improvement will be more obvious. In addition, the levels of microvessel density in the surface and deep layers of macula in the three groups were gradually increased [14]. This suggests that myopia is closely related to the change of microvessel density in macula, that is, with the increasing degree of myopia, the microvessel density in macula also shows a corresponding change.…”
Section: Methodsmentioning
confidence: 73%
“…If we use the combination therapy method, when using atropine eye drops, and also use OK lens or myopia defocus treatment, the choroidal thickening will be greater, and the effect of myopia improvement will be more obvious. In addition, the levels of microvessel density in the surface and deep layers of macula in the three groups were gradually increased [14]. This suggests that myopia is closely related to the change of microvessel density in macula, that is, with the increasing degree of myopia, the microvessel density in macula also shows a corresponding change.…”
Section: Methodsmentioning
confidence: 73%
“…In this context, we found that eyes with preoperative apical scarring were more likely to show improvements in visual acuity by the last postoperative visit than those without apical scarring. This observation suggests that in eyes with apical scaring there may be more room for improvement in visual acuity after initial corneal remodeling [25][26][27].…”
Section: Discussionmentioning
confidence: 96%
“…rigid gas permeable contact lenses) [24]. Another possible solution involves the use of intracorneal rings which can contribute to the stabilization of keratoconus [25,26]. The adequate treatment must be conducted in accordance with the severity level and only under the recommendation of an ophthalmologist.…”
Section: Introductionmentioning
confidence: 92%